Global champions of sustainable development - Flynn, Patricia M.; Gudić, Milenko; Tan, Tay Keong (Principles for Responsible Management Education (PRME) series, 2020)
"The 17 SDGs embody the collective aspirations of the world's peoples: peace, freedom, development, and sustainability. The challenges associated with the struggle for attainment of these goals and objectives are as diverse and complex as the variety of human societies, national conditions and natural ecosystems worldwide. The problems to be addressed range from extreme poverty and pandemics to racism and refugee crises. Some of the best strategies and solutions to these problems emerged from unlikely places; ranging from the corporate boardrooms and halls of administration to the fields of civic engagement and the vortices of crises. Often, a single person is the dauntless driving force behind these innovative programs and courageous experiments that made all the difference to the poorest and most disadvantaged social groups. Somehow, they were able to turn the abstract goals and principles of sustainability into concrete programs and effective action. This book, the first of its kind, offers a platform shares the individual experiences and personal studies of champions around the world that 'make sustainability work' in different contexts. In the trenches of practice, results are far from guaranteed, while sacrifice and obstacles are inevitable. These champions forge the paths forward - advocating ideas, mobilizing support, and exercising leadership - in diverse nations, organizations and communities. In their struggle, they develop plans and solutions that inevitably involve adaptation, sacrifice, trade-offs, and compromises that address the concerns of competing groups"--Provided by publisher.